Revisi Peta Distribusi Ikan Padi (Adrianichthyidae: Oryzias spp.) Berdasarkan Identifikasi Morfologi di Paparan Sunda Indonesia - Akhsan Fikrillah Paricahya; Kiki Nur Azam Kholil; Ifa Sufaichusan; Muh. Herjayanto; Rengga Retno Laila Saputri; Abd. Rahem Faqih; Agung Pramana Warih Marhendra (Jurnal Penelitian Pendidikan IPA, 2024)
Members of the Adrianichthyidae family share typical distributions, as does the javanicus group, which inhabits western parts of Southeast Asia. Javanicus group members, specifically Oryzias javanicus and Oryzias hubbsi, is the only Adrianichthyidae species that can be spotted in Sundaland Indonesia. Morphological identification and the species distribution mapping of Oryzias specimens from Sundaland in this study were interpreted using ecoregional and dendogram tree approach. Specimens were collected from 11 areas representing five ecoregions in Sundaland Indonesia. Specimens were collected from islands of Java, Sumatra, Belitung and Kalimantan. Six individuals from each population of Oryzias were sampled for morphological identification. Specimens collected from estuaries were morphologically identified as O. javanicus and specimens from freshwater identified as O. hubbsi. Distribution of O. hubbsi from Salatiga is the first record from Central East Java (CEJ) ecoregion, which was previously only distributed in Southern Sumatra-Western Java (SWJ) ecoregion. Morphology of O. hubbsi from Sundaland Indonesia has mean of Standard Length (SL) 1.56 cm, Total Length (TL) 1.94 cm, Anal rays (A) 16, Pectoral rays (P) 8, and Dorsal rays (D) 6. Meanwhile, morphology of O. javanicus from Sundaland has mean of SL 2.07 cm, TL 2.56 cm, A 22, P 11, and D 6.